Risk factors for surgical site infection (ssi) in post-appendectomy patients at Massenrempulu Hospital, Enrekang Regency, 2023 - Fahruddin, Annisa; Gani, Azis Beru; Harahap, Muhammad Wirawan; Purnamasari, Reeny; Mangarengi, Yusriani (Institute Of Computer Science (IOCS), 2025)
Surgical Site Infection (SSI) is a major healthcare-associated infection that significantly increases morbidity, mortality, and healthcare costs. This study aims to analyze the risk factors for SSI in post-appendectomy patients at Massenrempulu Hospital, Enrekang Regency, using a cross-sectional method with secondary data from patient medical records. A total of 41 patients met the inclusion criteria. The results indicate that SSI was more prevalent in females (65.9%) compared to males (34.1%), with the highest incidence occurring in the 17-25 age group (34.1%). In terms of nutritional status, most SSI cases were observed in patients with abnormal BMI, including underweight (22%), overweight (29.3%), and obesity (7.3%). Additionally, 92.7% of patients had no comorbidities, while a small percentage had hypertension (4.9%) or fatty liver disease (2.4%). Surgical duration was also a critical factor, as most SSI cases (92.7%) were associated with moderate-duration surgeries (60-120 minutes), while only 7.3% occurred in short-duration surgeries (<60 minutes). These findings highlight the importance of monitoring SSI risk factors, particularly among younger patients, females, and those with abnormal nutritional status. The study emphasizes the need for improved infection control strategies, proper nutritional management, and enhanced postoperative care to minimize SSI occurrence. Future research should consider primary data collection and additional variables to further explore risk factors. Additionally, healthcare facilities should enhance infrastructure and transition from manual to electronic medical records to improve patient management and reduce infection rates.